Mecanismos de disciplinamiento de la cultura en Frío y Subte de Rafael Pinedo - Pietrak, Mariola (Moderna Språk, 2024)
Rafael Pinedo’s trilogy, consisting of the novels Plop, Frío, Subte, presents various post-apocalyptic scenarios in which the end of culture as we know it becomes clear. In its place, other forms of culture are proposed - survival culture - which, in the almost caricatural dimension they take on, expose the disciplining mechanisms of culture, such as the repression of sexual instincts, the production of subjects, gender performativity. The post-apocalyptic strips social norms of their "normality" and allows us to see them in their raw, constructed and naturalised functioning, which - as this paper will argue - constitutes the end in itself of Pinedo’s work. With this in mind, I propose an approach to two novels by this Argentinean writer - Subte, Frío - as a laboratory in which the nature of gender and its role in the structures of culture are examined and debated.